ASSESSMENT OF MENSTRUAL HEALTH AND ANALGESICS USAGE IN YOUNG AGE WOMEN - AMEEN, ALMOHAMMADI; SUHAIL, JUNAID; LOUJAIN, SHORBATLI; AMAL, AL-SOMALI (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: The study focuses on assessing the incidence of menstrual irregularity among young women and the factors for a disturbance with the rationale to assess the use of analgesic drugs during Premenstrual Syndrome (PMS). Methods: A cross-sectional study was used. A total of 2500 randomly selected young female between the age of 11 and 30 y completed the study questionnaire to assess lifestyle pattern, variations in menstrual pattern, perceived stress, and to capture information about their menstrual cycle and related problems. In addition, the questionnaire assessed the use of analgesics for PMS. Results: 2481 participants completed the questionnaire. The mean age of participants’ menarche was 12.85±1.432 y. The prevalence of menstrual irregularities was 25.0 % (n=621) and about 8.5% (n=211) of respondents had severe pain that was not relieved by the use of analgesics. On the other hand, 50.9 % (n=1262) reported severe pain that was relieved by analgesics. A total of 1279 (51.6 %) of participants in this study used Over The Counter (OTC) analgesics to relieve PMS. Conclusion: Dysmenorrhea is the most common complaint among young females in Saudi Arabia. Low Body Mass Index (BMI), sedentary lifestyle, stress and early age of menarche are the most important factors associated with menstrual irregularities. Proper education programs and awareness among young girls about their menstrual health, and the provision of guidance in choosing effective analgesics and treatment options for dysmenorrhea are highly recommended.